2009
DOI: 10.1186/1472-6882-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Bach Flower Remedies for psychological problems and pain: a systematic review

Abstract: Background: Bach Flower Remedies are thought to help balance emotional state and are commonly recommended by practitioners for psychological problems and pain. We assessed whether Bach Flower Remedies (BFRs) are safe and efficacious for these indications by performing a systematic review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
1
29
0
3
Order By: Relevance
“…In another study, however, which also investigated the effect of Rescue essence on anxiety, no significant difference was observed between the group that used the essence or the placebo (16) . Also, a systematic review was found on the use of Bach flower remedies in psychological problems and pain (17) . The investigated databases were MEDlInE, Embase, AMED and Cochrane library, for papers published until July 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, however, which also investigated the effect of Rescue essence on anxiety, no significant difference was observed between the group that used the essence or the placebo (16) . Also, a systematic review was found on the use of Bach flower remedies in psychological problems and pain (17) . The investigated databases were MEDlInE, Embase, AMED and Cochrane library, for papers published until July 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention time ranged from three hours to three months and the number of volunteers between 40 and 110 people. These studies were developed in England, Germany, Israel and the United States (17) . In Brazil, floral therapy has increasingly gained ground.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rescue Remedy is a 5 · (Homeopathic Pharmacopoeia of the United States) dilution of flower essences from impatiens (Impatiens gladulifera), Star of Bethlehem (Orithogalum umbellatum), cherry plum (Prunus cerasifera), rock rose (Helianthemum), and clematis (Clematis vitalba). 31 Rescue Remedy is indicated for use in stressful situations or in times of crisis. 31 This should not be primary therapy, but may be added during recovery time at provider discretion.…”
Section: Order Treatmentsmentioning
confidence: 99%
“…31 Rescue Remedy is indicated for use in stressful situations or in times of crisis. 31 This should not be primary therapy, but may be added during recovery time at provider discretion.…”
Section: Order Treatmentsmentioning
confidence: 99%